Inter-University Management: Action plan for the improvement of the integrated solid waste management in the Guácimo Canton, Limón, Costa Rica - Campos Rodríguez, Rooel (2015)
This article reports the main findings of a research conducted in the field of environmental education, as a contribution to inter-university management. Three state universities that are part of the Costa Rican educational system participated in the execution of this study: Instituto Tecnológico de Costa Rica (TEC), Universidad de Costa Rica (UCR) and Universidad Nacional (UNA). The general objective aims at proposing an environmental model for adequate solid waste management in Guácimo canton, located in the province of Limón, Costa Rica, and offering inputs for university management in this field. The research was carried out following a mixed approach, and one of the main findings indicates that the environmental issue in the region under study is multivariate, including aspects such as politics, administrative difficulties, planning problems, lack of investment, absence of management plans and controls, as well as low coverage of collection ctivities, absence of appropriate places for treatment of waste and few training opportunities in the area of environmental education and health. These aspects are addressed from the inter, multi, transdisciplinary and interuniversity management viewpoints.